Freedom of choice of law applicable to the international contract in Colombian private international law - Oviedo Albán, Jorge (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This article analyzes the freedom of choice of law applicable to international contracts in Colombian Private International Law. In the first part, reference is made to the different theses existing in the doctrine in relation to the interpretation of the norms contained in the Civil Code and the Commercial Code. Subsequently, the judicial decisions that have interpreted the Colombian rules of Private International Law are identified, concluding that it is possible to choose the law that will regulate the international contract. In a second and third point, the rules on international arbitration and on the international sale of goods are described, to conclude that there is a legal system in Colombia favorable to the freedom of choice of law applicable to international contracts.